Piecewise function parameters as responses of the design of experiment in the development of a pulsatile release chronopharmaceutical system - Vonica-Gligor Andreea Loredana; Tomuţă Ioan; Leucuţa Sorin E. (Acta Pharmaceutica)
The aim of this work was to develop a pulsatile release system with metoprolol for chronotherapeutical use by coating swellable mini-tablets with Eudragit RS. To study the influence of the formulation factors (amount of coating polymer, plasticizer percentage in film coating and swelling agent percentage in mini-tablets), a Box-Behnken design of experiment (DoE) was used. To evaluate the influence of the studied factors on the sigmoid shape of the dissolution profile, piecewise function parameters were used as the responses of DoE. The results show that higher concentrations of coating polymer and higher concentrations of plasticizer polymer led to a thicker and more elastic polymeric film, which led to a delay in drug release. Using the parameters of the piecewise function as DoE responses, an optimum formulation with a sigmoid shape dissolution profile and a 2.5-h lag time followed by rapid drug release were obtained.